Transport and thermoelectric properties of melt spinning synthesized M2FeNiSb2 (M = Ti, Hf) double half Heusler alloys. (August 2023) - Hassan, Mohamed Asran; El-Khouly, A.; Elsehly, E.M.; Almutib, Eman N; Elshamndy, Samah K.; Serhiienko, I.; Argunov, E.V.; Sedegov, A.; Karpenkov, D.; Pashkova, D.; Gorshenkov, M.; Novitskii, A.; et al.
Highlights: P-type Hf2 FeNiSb2 and Ti2 FeNiSb2, prepared by melt spinning method. The samples sintered with spark plasma. Thermoelectric properties were studied as functions of temperature from 300 K to 900 K. Morphology and grain sizes were examined by SEM analysis. The maximum seebeck coefficient was obtained for Ti2 FeNiSb2 with a value of 293µV/K at 575 K. The maximum zT value at 874 K was achieved for Hf2 FeNiSb2 sample. Abstract: In this study, we report on structural and thermoelectric properties of novel Heusler compounds Hf2 FeNiSb2 and Ti2 FeNiSb2 . Polycrystalline samples were successfully synthesized by arc melting and melt spinning techniques and consolidated by spark plasma sintering method. The studied compounds were found to crystallize in a face centered cubic crystal structure, as can be judged by superstructural reflections, clearly seen on the X-ray diffraction patterns. Morphology and grain sizes were examined by SEM analysis, showing homogeneity and high density of grains in the synthesized samples. Electrical conductivity and Seebeck coefficient were investigated in a range of temperatures between 300 and 900 K. Thermal conductivity was measured in the same temperature range and found to be significantly lower than that previously reported for related half-Heusler alloys such as TiCoSb. The thermoelectric figure of merit of the concerned Hf2 FeNiSb2 and Ti2 FeNiSb2 samples was found at 0.082 and 0.027, respectively, at 874 K. Graphical abstract: Image, graphical abstract